Welcome to The Backyard: Introducing Calgary's First Laneway Activation Project (breakout presentation). (December 2017) - Craig, Will
Abstract : Background: Come on over….to Calgary's backyard. It's about everyday experiences: walking the dog, riding your bike, making your way over to meet friends. We are bringing the lane to life. Linger in a pop up patio, enjoy BBQ, shoot some hoops, practice yoga, peruse the local marketplace or enjoy local fayre. Watch local bands and artists performing or settle in for an outdoor movie. It's a shared place for people, and everyone's invited! Description of Program: This is a pilot initiative as part of the City of Calgary's effort to support businesses that are feeling the effects of street upgrades along 17th avenue. The laneway revitalization will increase available frontage for these businesses and provide a shared space for the public and patrons to enjoy. In the spirit of local community enterprise, many local partners have come together to create the environment and orchestrate the event over two weekends in September. Aims: 1) Bring the laneway to life! 2) Realize Calgary's first official laneway activation project 3) Create a thriving backyard space for Calgary's art, culture and local businesses to flourish, and 4) pilot the project as a test case for future urban interventions in Calgary. Method: All interventions in the laneway are convertible and temporary and components are a modular design, opening possibilities for future re-use and re-interpretation. Implications: Come on down and see the results for yourself! The Backyard will be open September 22nd – 24th and September 29th – October 1st.